Pelatihan dan Pendampingan Persiapan Homestay untuk Akomodasi Wisatawan Di Desa Bonjeruk, Lombok Tengah - Permadi, Lalu Adi; Tara, Nur Aida Arifah; Oktaryani, G A Sri; Rispawati, Dewi; Febrianik, Nanik; Agustina, Mirna (Jurnal Gema Ngabdi, 2025)
The urgency of this community service is a critical endeavor to empower local communities to maximize the potential of tourism by leveraging local wisdom and enhancing their economic capacity. The objective of this service is to enhance the management capabilities of the Tourism Awareness Group and to broaden the perspective of POKDARWIS WPJ members on homestays and accommodation in general. The objective is to convert homestays into accommodations that adhere to high-quality service standards through the implementation of continuous training and mentoring. The WPJ Tourism Awareness Group is expected to achieve the following objectives: the group will effectively manage and develop at least one homestay, as well as the group's organizational administration, all while preserving the economic potential of the local community as a source of sustainable income. Consequently, it is anticipated that this initiative will initiate a positive cascading effect that will extend beyond the accommodation sector to encompass the entire local tourism ecosystem.